2008
DOI: 10.1016/j.seizure.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of epilepsy in Hong Kong SAR, China

Abstract: The prevalence of epilepsy in HKSAR is more common than previously thought. The data retrieved is useful for planning and allocation of health resources for patients with seizure disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 27 publications
2
22
1
Order By: Relevance
“…These observations are in agreement with the studies by various authors who have found 10-30 years as the most common age group (11)(12)(13)(14)(15) and the range of patients with generalised seizures between 50-69%, while 31-50% had partial seizures. (14,(16)(17)(18)22).…”
Section: Discussionsupporting
confidence: 93%
“…These observations are in agreement with the studies by various authors who have found 10-30 years as the most common age group (11)(12)(13)(14)(15) and the range of patients with generalised seizures between 50-69%, while 31-50% had partial seizures. (14,(16)(17)(18)22).…”
Section: Discussionsupporting
confidence: 93%
“…In most total population studies, incidence of epilepsy or of unprovoked seizures is higher in males than in females. This seems true even after the higher incidence in males of definitive risk factors for epilepsy (i.e., head injury, stroke, central nervous system infection) is taken into account [6][7][8][9][10][11][12]47,48 . For most but not all incidence studies, sex-specific differences in incidence are not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of epilepsy varies worldwide 3 with a higher prevalence in developing countries [4][5][6] . The life time prevalence of epilepsy also varies from 1.5 to 14 per 1000 population among different countries [7][8][9][10][11][12][13][14][15] . More than half of the 50 million people with epilepsy worldwide live in Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…32 Prevalence among Caucasians was determined by a study of the Norwegian National registry in 2015, 33 and East Asian prevalence by a study of the regional registry of patients older than 15 years in Hong Kong, China. 34 Another estimate of Southeast Asian prevalence was produced via a random cluster survey of Cambodian villages. 35 Differing in methodology and ascertainment and not ideally race-matched to JME index cases studied, these studies represent the only data we could use to compare allele frequencies of EFHC1 variants with JME disease prevalence.…”
Section: Allele Frequenciesmentioning
confidence: 99%